2021
DOI: 10.1021/acs.biomac.1c01158
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis of Polyphenol Spheres via Amine-Catalyzed Polymerization-Induced Self-Assembly

Abstract: A facile and general strategy for preparing uniform and multifunctional polyphenol-based colloidal particles through amine-catalyzed polymerization-induced self-assembly is described. The size and interfacial adhesion of polyphenol spheres can be easily controlled over a wide range via adjusting the concentration of the cosolvent and monomer. Moreover, the polyphenol spheres showed excellent thermal and chemical stability and highly active properties and could efficiently deplete the reactive oxygen species (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…Briefly, dual-soft-template surfactants Pluronic F127 and P123 assemble in about 7–14 nm cylindrical micelles (Figures S1 and S2) in different ethanol/water mixtures and then larger-sized P123+F127/TMBZ/PG composite micelles (Figures S3 and S4) are formed with the addition of phloroglucinol (PG) and hydrophobic TMBZ. Following this, ethylenediamine (EDA) is added to trigger PISA via Michael addition and Schiff base reactions to get polyphenol-based spheres . The polymerization reaction process can be observed from the significant color change (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, dual-soft-template surfactants Pluronic F127 and P123 assemble in about 7–14 nm cylindrical micelles (Figures S1 and S2) in different ethanol/water mixtures and then larger-sized P123+F127/TMBZ/PG composite micelles (Figures S3 and S4) are formed with the addition of phloroglucinol (PG) and hydrophobic TMBZ. Following this, ethylenediamine (EDA) is added to trigger PISA via Michael addition and Schiff base reactions to get polyphenol-based spheres . The polymerization reaction process can be observed from the significant color change (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, when an insufficient amount of PG (4 mg/mL) was used, the corresponding P123+F127/TMBZ/PG composite emulsions preferred merging and fusing into colloidal particles (Figure S19). In contrast, when a sufficient amount of PG (8 mg/mL) was used, the spiral multishelled hollow nanostructured carbon materials could be obtained (Figure S20), which demonstrates that the Michael addition and Schiff base reactions between PG and amines can facilitate further crystallization of polyphenol oligomers. , These might be due to the corresponding increase in the hydrogen-binding interactions between the P123+F127/TMBZ/PG composite emulsions and PG/EDA aggregates. Furthermore, by continuously decreasing the stirring rate from 800 to 600 or 400 rpm, an irregular nonporous structure appeared (Figures S21 and S22).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have demonstrated that PISA is applicable not only to reversible deactivation radical polymerization (RDRP) but also to other polymerization mechanisms, especially ring-opening metathesis polymerization-induced self-assembly (ROMPISA), , polymerization-induced particle assembly (PIPA), and CuAAC click polymerization-induced self-assembly (CPISA) . Poly­(polyphenol) materials, due to strong covalent bond and noncovalent bond interaction during polyphenol polymerization, have been prepared which have various morphologies and functions. Recently, Sheng et al reported the synthesis of polymeric Janus nanosheets by polymerizing dopamine with the octadecylamine template. The interactions during polyphenol polymerization can be involved in the morphology evolution of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%